2013
DOI: 10.1989/ejihpe.v3i3.49
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about gender violence. Sexism in adolescent relationships

Abstract: This paper explores the relationships in adolescence, examining beliefs about gender violence from a cognitive-developmental perspective. The sample consists of 297 students from 3 different state-subsidized schools, between the ages of 13-18 (2nd and 4th years of Secondary Education and 2nd year of High School). The students’ representations of relationships are analyzed from the point of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…These data are consistent with the findings of Price et al [ 56 ], who concluded that both boys and girls were more accepting of female violence than male violence, with boys offering a higher level of justification. Others [ 57 ] have also found that boys were more likely than girls to justify physical dating violence as a method of defence. Likewise, previous authors [ 58 ] concluded that girls justify their aggressions more as an outburst of anger (girls, 22.4% vs. boys, 13.9%), while boys do it to defend themselves from an earlier aggression (girls, 6.6% vs. boys, 13.0%).…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with the findings of Price et al [ 56 ], who concluded that both boys and girls were more accepting of female violence than male violence, with boys offering a higher level of justification. Others [ 57 ] have also found that boys were more likely than girls to justify physical dating violence as a method of defence. Likewise, previous authors [ 58 ] concluded that girls justify their aggressions more as an outburst of anger (girls, 22.4% vs. boys, 13.9%), while boys do it to defend themselves from an earlier aggression (girls, 6.6% vs. boys, 13.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Por tanto, es un periodo crucial para el establecimiento de relaciones de género porque se produce la consolidación de las habilidades, la expansión de las relaciones entre iguales y la construcción de nuevas redes sociales y de parejas sentimentales (Ramiro-Sánchez et al, 2018;Rebollo-Catalán et al, 2017). Diversas investigaciones realizadas con población adolescente española (véase Azorín, 2017;Calvo, 2018;Carrera-Fernández et al, 2017;De la Osa et al, 2015), así como en otros países de habla hispana (por ejemplo, Hernández y González, 2016), muestran que existe desigualdad y falta de equidad en las relaciones de género y en la vida sexual de la población adolescente. Otros estudios, como el de Gutiérrez et al (2019), en cambio, sostienen que en los países occidentales las formas tradicionales de comportamientos sexistas son poco habituales y que las concepciones del sexismo basadas en diferencias biológicas han evolucionado hacia otras formas de "sexismo benevolente" (Glick y Fiske, 1996).…”
Section: Introductionunclassified